Mopping Up Spilt Religion: The Problem of Enthusiasm - Mee, Jon (Romanticism on the Net)

(untitled) (Université de Montréal, 2002)
Abstract"Enthusiasm" is a term to which Romantic criticism is blind. Where it is noticed, it is usually assumed that over the course of the eighteenth century it was rehabilitated. Whereas it had been associated with the violence and excess of the sects in the Civil War, it came to be identified with the healing powers of emotion and imagination. This essay argues for a more complicated understanding of the term's trajectory. The prohibition of enthusiasm found, for instance, in Locke comes to be replaced by a more regulatory discourse. From this perspective, its benefits had to be harnessed, but there remained a powerful awareness that poetic or noble enthusiasm could easily degenerate into its vulgar and dangerous avatar. These fears were intensified in the 1790s by Burke's representation of revolutionary transparence as a throwback to seventeenth-century puritanism. Poets such as Coleridge, whose case history provides the final section of this essay, inherited this complex understanding of the term. Coleridge came increasingly to distinguish a healing "enthusiasm" from the "fanaticism" of the mob, but desynonymization could never quite eradicate the fear that the fountains within of the former were deeply linked to the destructive energies of the latter.